Accounting Reality Behind Waste Scales - Paranoan, Selmita; M. Yusuf, Rolland; Yamin, Nina Yusnita (Universitas Muhammadiyah Yogyakarta, 2025)
This research is based on the rampant scattering of waste, which is no longer considered valuable, so it ends up in landfills. This research focused on the accounting reality of the waste business in the Kawatuna landfill area. This research used a qualitative method with an ethnomethodology approach and data collection techniques in the form of observation, interviews, and documentation to observe the professional behavior of waste pickers and collectors in practicing waste transactions. The results showed that accounting practices in waste transactions support sustainable business relationships in the Kawatuna landfill area. Mutual trust is the main key to building a waste business with the recognition of waste as a valuable asset. The practice of debt and credit that occurs supports simple accounting practices in the waste business. This finding is relevant to the concept of circular economy; the application of the concept supports business processes that involve economic, environmental, and social spheres in forming sustainable businesses.